2022
DOI: 10.24840/2183-6493_008.005_0002
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Ellagic Acid from Chestnut Shell as a Natural Anti-anxiety Food Supplement

Abstract: Mental health is on the agenda, especially in times of pandemic due to the COVID-19 virus. Nowadays, psychological problems, such as anxiety and depression, have been more discussed and have become even more critical during confinement. This paper proposes the development process of an innovative product whose active ingredient - ellagic acid, extracted from the chestnut shell - has anxiolytic properties and can be potentially used in consumers' daily lives, preventing this type of illness. The product present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…EA's extreme antioxidant and anti-inflammatory properties have been the first choice for many studies, and it has been shown that EA can be used to treat depression by modulating the apoptotic pathway, inhibiting mitogen-activated protein kinase (MAPK) and triggering inflammatory mediators, among other mechanisms, reduced the number of brain infarcts and apoptotic cells and improved symptoms such as anxiety, depression-like motor and exploratory behavioural disturbances that had been present [48]. EA extracted from chestnut shells similarly confirms its anxiolytic properties to prevent such disorders [49]. EA is also currently being used in clinical trials to combat negative mental conditions such as depression and anxiety as well as being found to have a significant positive effect on improving sleep and reducing the production and concentration of pro-inflammatory cytokines in patients [50].…”
Section: Treatment For Depressionmentioning
confidence: 99%
“…EA's extreme antioxidant and anti-inflammatory properties have been the first choice for many studies, and it has been shown that EA can be used to treat depression by modulating the apoptotic pathway, inhibiting mitogen-activated protein kinase (MAPK) and triggering inflammatory mediators, among other mechanisms, reduced the number of brain infarcts and apoptotic cells and improved symptoms such as anxiety, depression-like motor and exploratory behavioural disturbances that had been present [48]. EA extracted from chestnut shells similarly confirms its anxiolytic properties to prevent such disorders [49]. EA is also currently being used in clinical trials to combat negative mental conditions such as depression and anxiety as well as being found to have a significant positive effect on improving sleep and reducing the production and concentration of pro-inflammatory cytokines in patients [50].…”
Section: Treatment For Depressionmentioning
confidence: 99%